1983
DOI: 10.1073/pnas.80.21.6431
|View full text |Cite
|
Sign up to set email alerts
|

The dnaK protein of Escherichia coli possesses an ATPase and autophosphorylating activity and is essential in an in vitro DNA replication system.

Abstract: The Escherichia coli dnaK gene product, originally defined by mutations that blocked A phage DNA replication, is known to be necessary for E. coli viability. We have purified dnaK protein to homogeneity and have demonstrated that it possesses a weak DNA-independent ATPase activity, which results in the production of ADP and Pi. The proof that this ATPase activity is encoded by the dnaK+ gene relies primarily on the fact that the dnaK756 mutation results in the production of an ATPase activity with altered phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
141
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(150 citation statements)
references
References 26 publications
9
141
0
Order By: Relevance
“…2, the ATP-agarose affinity column is most effective in achieving the purification of the proteins, a result whose merit is obvious. It should also be pointed out that other laboratories have reported that the Escherichia coli DNA K protein, which by DNA sequence analysis has been shown to be 50% homologous to the Drosophila 70-kDa heat-shock protein (3), possesses both weak ATPase and autophosphorylating activities and appears to be involved in the replication of bacteriophage lambda DNA in infected cells (28,29). In the case of the mammalian 72-and 73-kDa proteins, we have tested the ability of the purified proteins to either hydrolyze ATP in vitro or to autophosphorylate.…”
Section: Resultsmentioning
confidence: 99%
“…2, the ATP-agarose affinity column is most effective in achieving the purification of the proteins, a result whose merit is obvious. It should also be pointed out that other laboratories have reported that the Escherichia coli DNA K protein, which by DNA sequence analysis has been shown to be 50% homologous to the Drosophila 70-kDa heat-shock protein (3), possesses both weak ATPase and autophosphorylating activities and appears to be involved in the replication of bacteriophage lambda DNA in infected cells (28,29). In the case of the mammalian 72-and 73-kDa proteins, we have tested the ability of the purified proteins to either hydrolyze ATP in vitro or to autophosphorylate.…”
Section: Resultsmentioning
confidence: 99%
“…Along with VirB4 and the CP (VirD4), VirB11 is thought to energize the type IV secretion machinery either for complex assembly, pilus production and/or substrate secretion. The NTPase activity of several VirB11-like proteins has been determined in vitro (Christie et al, 1989;Krause et al, 2000b;Rivas et al, 1997;Sexton et al, 2004), revealing a rather weak activity similar to the one observed for chaperons like DnaK (Zylicz et al, 1983). VirB11 of A. tumefaciens has been reported to additionally possess an autophosphorylation activity (Christie et al, 1989), however, such an activity was not detected for any other member of the family of VirB11-like proteins.…”
Section: Virb11: a Ring-shaped Cytoplasmic Ntpase Fuelling The Secretmentioning
confidence: 94%
“…DnaK is an abundant, consitutively expressed protein with an apparent molecular weight of 70 000. The purified protein (ZYLICZ and GEORGOPOULOS 1984) possesses a weak ATPase activity (with a turnover number of about one ATP per minute) and can be autophosphorylated at threonine residues (ZYLICZ et al 1983). Its enzymatic activities are well studied (CEGIELSKA and GEORGOPOULOS 1989;DALIE et al 1990).…”
Section: Dnak-the Prokaryotic Homologuementioning
confidence: 99%
“…Its enzymatic activities are well studied (CEGIELSKA and GEORGOPOULOS 1989;DALIE et al 1990). The ATPase is DNA independent, but is modulated by AO and AP proteins in vitro and in vivo (ZYLICZ et al 1983). In contrast to ATP binding, ATP hydrolysis and the autophosphorylating activity depend on divalent cations (CEGIELSKA and GEORGOPOULOS 1989;DALIE et al 1990).…”
Section: Dnak-the Prokaryotic Homologuementioning
confidence: 99%